Corrosion and environmental impacts during the flowback water disposal associated with the Bakken shale. (1st April 2018) - Chilkoor, Govinda; Shrestha, Namita; Soeder, Daniel; Gadhamshetty, Venkataramana
Graphical abstract: Highlights: Flowback water transport poses specific environmental challenges. Bakken flowback water aggravate corrosion of mild steel pipelines. Flowback water induce uniform and pitting corrosion under a range of pH conditions. Flowback water favors the growth of Iron oxy-hydroxide crystals. Abstract: This study investigates the flowback water impacts on the corrosion of mild steel pipelines used to transport the saline wastewater generated during fracturing of the Bakken shale. The uniform corrosion rates were high under acidic conditions compared to those under neutral and alkaline conditions. The pitting attack on the flowback water pipelines was 100-fold and 10-fold higher for acidic and alkaline conditions, respectively, than those for the neutral conditions. The corrosion deposits on the mild steel were characterized by a large specific surface area and high reactivity. These results suggest that the flowback water pipelines become a potential source of contaminants that threaten agricultural land and water resources.